American palms used for medicine, in the ethnobotanical and pharmacological publications - Sosnowska, Joanna (2008)
The center of diversity of palms (Arecaceae) in tropical America is found in the Amazon basin and along the Panamanian isthmus.The greatest palm species richness has been reported for the Iquitos and Chocó areas. Many species of palms are used mainly for construction and due to their edible fruits. In addition, there are 104 palm species that are used for medicinal purposes in many regions of the Americas. Cocos nuciferaand Oenocarpus batauaare the most commonly used species for medicinal purposes. The fruit is the most commonly used part of palms for medicinal purposes (57 species). The traditional and medicinal use of plants has deep roots in indigenous communities of Latin America. The significance of ethnomedicine for health care of local populations can not be ignored anymore because it plays a significant role in basic health care in developing countries. Interdisciplinary research in antropology, ethnobotany and ethnopharmacology helps gather information on ethnomedicine and design new drugs for modern medicine. American palms are sources of useful bioactive compounds against diabetes, prostate hyperplasia and leishmaniasis.